PHYSIOTHERAPEUTIC ACTIVITY IN THE TREATMENT OF PENETRAL GENE PAIN / PENETRATION WITH A FOCUS ON THE MANUAL THERAPY APPROACH IN WOMEN AT MENACME - Sant’Anna Cunha, Caroline (Health and Society, 2021)
Genital-pelvic pain / penetration disorder (DGPP) includes vaginismus, dyspareunia and vulvodynia, where the following symptoms are present: Presence of fear or anxiety related to vulvovaginal or pelvic pain in anticipation, during or as a result of vaginal penetration, in addition to the presence of tension or hardening of the pelvic floor muscles during the attempt of vaginal penetration. Adequate sexual function is considered an important factor for quality of life, being recognized by WHO (World Health Organization) regarding the presence of sexual dysfunction as a public health problem, recommending its investigation for causing important changes in quality of life and in the relationship with your partner. It is identified that the role of the physiotherapist becomes relevant in the process of identification and rehabilitation of genito-pelvic pain, justifying the importance of studies on this topic. In order to analyze the role of the physiotherapist in the treatment of pelvic genital pain / penetration with a focus on the approach of manual therapy in women at menacme, a narrative review of the literature was carried out, where 17 articles were used as a basis for research and data collection. During the analysis of the articles, it was defined that DSFs tend to appear in the female fertile phase, causing pain and discomfort. In the reviews covered in this study, it was analyzed that DGPP is a complex syndrome in which the sensation and intensity of pain are felt in different places. With this the diagnosis becomes difficult taking into account the shame and / or blocking of the woman in reporting a sexual complaint. Through a physical therapy assessment, in order to check the tone and function of the pelvic floor muscles, the existence and location of tender points, as well as the understanding of voluntary contractions and rests of these muscles, a therapeutic planning with the use of interventions is outlined. specific measures in self-relaxation and anxiety control techniques, improving body awareness. It is concluded that there is effectiveness in exploring self-knowledge to improve the quality of life of women who suffer from this problem, providing positive results in a short period, thus contributing to the improvement of the sexual function of women with DSFs (Female Sexual Dysfunctions).